Aplysia gigantea toxicosis in 72 dogs in Western Australia. Issue 7 (20th June 2013) - Peacock, RE; Hosgood, G; Swindells, KL; Smart, L
<x xml:space="preserve">Abstract</x> Objectives This study aimed to: (1) confirm a temporal association between exposure to the sea hare Aplysia gigantea and the development of a neurotoxicosis in dogs and (2) further characterise the clinical signs, treatment and outcomes in dogs with this suspected toxicosis. Methods The medical records from four veterinary practices within the Geraldton region of Western Australia were searched for dogs that had been exposed to A. gigantea and subsequently presented to a veterinarian during the period of January 2001 to March 2011. Signalment, exposure history, clinical signs, treatment and outcome were recorded. Results In total, 72 dogs met the inclusion criteria. Clinical signs included ptyalism, emesis, ataxia, hyperaesthesia, tremors, muscle fasciculations, seizures, nystagmus and respiratory distress; 30 dogs did not have abnormal clinical signs at presentation; 69 dogs were presented during January to April. Treatment included gastrointestinal and dermal decontamination, and supportive management of seizures, tremors and muscle fasciculations. Of the 72 dogs, 65 survived to discharge, 4 died and 3 were euthanased. Information from subsequent examinations was available for 57 dogs and no long‐term complications were reported. Conclusions Exposure to A. gigantea was temporally associated with the development of neuroexcitatory clinical signs in dogs. Gastrointestinal and respiratory signs also occurred in some dogs. Dogs with suspected toxicosis were presented mostly in the months of January to April. The proportion of dogs that died or were euthanased because of worsening clinical signs was approximately 10%.